2021
DOI: 10.1016/j.jfma.2020.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation programs for patients with COronaVIrus Disease 2019: consensus statements of Taiwan Academy of Cardiovascular and Pulmonary Rehabilitation

Abstract: The COronaVIrus Disease 2019 (COVID-19), which developed into a pandemic in 2020, has become a major healthcare challenge for governments and healthcare workers worldwide. Despite several medical treatment protocols having been established, a comprehensive rehabilitation program that can promote functional recovery is still frequently ignored. An online consensus meeting of an expert panel comprising members of the Taiwan Academy of Cardiovascular and Pulmonary Rehabilitation was held to provide recommendation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 49 publications
(62 reference statements)
0
33
0
9
Order By: Relevance
“…Thus, respiratory rehabilitation becomes an attractive strategy in the management of these patients, since it has been observed that pulmonary rehabilitation is effective at improving respiratory function (and, therefore, functional capacities) in different respiratory disorders, such as chronic obstructive pulmonary disease (COPD) or asthma, among others [ 7 , 8 , 9 ]. Indeed, it has been argued that rehabilitation programs that aim to improve the function of the respiratory system should be included in the management of patients with COVID-19 [ 10 , 11 , 12 ]. However, to our knowledge, only one randomized controlled trial studied the effects of respiratory rehabilitation in people infected with COVID-19, and they were elderly subjects [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, respiratory rehabilitation becomes an attractive strategy in the management of these patients, since it has been observed that pulmonary rehabilitation is effective at improving respiratory function (and, therefore, functional capacities) in different respiratory disorders, such as chronic obstructive pulmonary disease (COPD) or asthma, among others [ 7 , 8 , 9 ]. Indeed, it has been argued that rehabilitation programs that aim to improve the function of the respiratory system should be included in the management of patients with COVID-19 [ 10 , 11 , 12 ]. However, to our knowledge, only one randomized controlled trial studied the effects of respiratory rehabilitation in people infected with COVID-19, and they were elderly subjects [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…У больных с тяжелым течением COVID-19, пожилого возраста (≥70 лет), с ожирением, СД, ИМ и инсультом в анамнезе, другими ССЗ, органной недостаточ ностью одного или более органов к определению срока начала реабилитации следует подходить очень осторожно. При легкой форме COVID-19 больные вовлекаются в самостоятельное осуществление мероприятий по медицинской реабилитацию в домашних условиях с 8-10-го дня от момента появления симптомов, при отсутствии лихорадки без приема жаропонижающих препаратов не менее 24 ч и выраженной слабости в предыдущие 2 дня, а также других симптомов, связанных с COVID-19 [61][62][63][64]. Некоторые лекарства (противовирусные препараты), применяемые для лечения COVID-19, вызывают удлинение интервала QT, нарушение проводимости и развитие желудочковой тахикардии по типу пируэт.…”
Section: сроки начала реабилитации и противопоказанияunclassified
“…При легкой форме COVID-19 больные вовлекаются в самостоятельное осуществление мероприятий по медицинской реабилитации в домашних условиях с 8-10-го дня от момента появления симптомов, при отсутствии лихорадки без приема жаропонижающих препаратов не менее 24 ч и выраженной слабости в предыдущие 2 дня, а также других симптомов, связанных с COVID-19 [62][63][64][65].…”
Section: сроки начала реабилитации и противопоказанияunclassified